Enhancement of Antitumor Vaccination by Targeting Dendritic Cell-Related IL-10 - Llopiz, Diana; Ruiz, Marta; Silva, Leyre; Sarobe, Pablo (Frontiers in Immunology, 2018)
Understanding mechanisms associated to dendritic cell (DC) functions has allowed developing new antitumor therapeutic vaccination strategies. However, these vaccines have demonstrated limited clinical results. Although the low immunogenicity of tumor antigens used and the presence of tumor-associated suppressive factors may in part account for these results, intrinsic vaccine-related factors may also be involved. Vaccines modulate DC functions by inducing activating and inhibitory signals that determine ensuing T cell responses. In this mini review, we focus on IL-10, inhibitory cytokine induced in DC upon vaccination, which defines a suppressive cell subset, discussing its implications as a potential target in combined vaccination immunotherapies.